Histopathological and apoptotic examination of zebrafish (Danio rerio) gonads exposed to triclosan - Akbulut Cansu (Archives of Biological Sciences, 2021)
Triclosan, produced as a broad-spectrum antibiotic in the early 1960s, is generally used as a preservative in personal care products, fabrics, plastic products such as kitchenware and toys. As a result of the high demand for triclosan, this chemical threatens the aquatic ecosystem by contaminating wastewater sources. Environmental pollutants affect the reproductive potential of fish, one of the most critical aquatic organisms. This study aimed to investigate the histopathological and apoptotic effects of triclosan in zebrafish gonads. Fish were exposed to sublethal concentrations of triclosan for 5 days, and general histological methods were applied. Histological sections were examined under a light microscope after staining with hematoxylin and eosin and toluidine blue. Triclosan exposure caused deterioration in ovarian tissue, such as shrinkage in the ooplasm, accumulation of proteinaceous fluid in the interstitial tissue, morphological changes of oocyte and the zona radiata. In testicular tissue, triclosan exposure caused fusion in seminiferous tubules, hypertrophy in spermatogenic and Leydig cells, edema in seminiferous tubules, and karyorrhexis in spermatogenic cells. The TUNEL assay was used for the determination of apoptotic cells. Brown-colored apoptotic cells were visualized under the light microscope. TUNEL positive cells were observed in all exposure groups. Triclosan administration was found to cause apoptosis in zebrafish gonads. These findings indicate that triclosan potentially affects fish reproduction, and that its judicious disposal is essential for protecting the environment and maintaining the reproductive potential of fish.